Polycystic ovary syndrome and periodontal status: a literature review - I. A. Igumnov (Scientific Сentre for Family Health and Human Reproduction Problems, 2017)
The review considers the problem of connection the polycystic ovarian syndrome and periodontal disorders of the fertile women. The authors marked that this problem is not virtually touched upon in Russian science. In the foreign literature this issue is discussed in connection with studying the micro-biome and oxidative stress. The authors refer to some articles showing that the quantity of pathogenic microorganisms responsible for periodontal disorders and the level of specific antibodies in blood serum are increased in women with polycystic ovarian syndrome, especially in the cases of gum inflammation. Also the article gives the data where the results show the wider spreading of periodontal disorders in women with polycystic ovarian syndrome in comparison with the healthy ones where controls were matched by age and BMI. The authors think that studies on oral microbiocenose disorders and tissue quality of periodontium of the fertile women with polycystic ovarian syndrome are quite important. The further studying of connection of polycystic ovarian syndrome and oral mucous membrane inflammation could reveal definite periodontal pathogens, which can influence systematic inflammation processes in polycystic ovarian syndrome.